Effect of TPACK-Based Guided Inquiry with Geogebra on Mathematical Concept Understanding Ability - Susilo Adi Prayoga; Nurul Husnah Mustika Sari (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2026)
The low ability of students' mathematical conceptual understanding remains a persistent challenge in mathematics learning, including at SMP Negeri 1 Pekalongan on the topic of geometric transformation. The purpose of this study is to investigate the influence of a GeoGebra-assisted guided inquiry learning model based on TPACK on the mathematical conceptual understanding of ninth-grade students, particularly on the subtopics of translation and dilation. A quantitative research method was adopted in this study, utilizing a quasi-experimental framework in the form of a nonequivalent control group design. Samples were selected using cluster sampling, consisting of 31 students of class IX B as the experimental group and 32 students of class IX A as the control group. The instrument used was a multiple-choice test that had been validated for validity and reliability. Validity was tested using the Pearson Product Moment method, resulting in 15 out of 20 items declared valid for both the pretest and posttest (r-table = 0.349, df = 30, α = 5%). Reliability was measured using Cronbach's Alpha, yielding a coefficient of 0.714 (pretest) and 0.860 (posttest), both categorized as high reliability. Data were analyzed using an initial similarity t-test on pretest data to verify the equivalence of both groups prior to treatment, followed by the Mann-Whitney U test and N-Gain analysis on posttest data to examine group differences and measure the degree of improvement in students' mathematical conceptual understanding. The Mann-Whitney U test yielded an Asymp. Sig. (2-tailed) value of 0.026, which is below the significance level of 0.05, indicating a significant difference between the mathematical conceptual understanding of the experimental and control groups. The average N-Gain score of 0.5397 reflects a moderate level of improvement. Therefore, the GeoGebra-assisted guided inquiry learning model based on TPACK significantly affects students' mathematical conceptual understanding.